Poverty and economic growth in Swaziland - Nindi, Angelique G. (Managing global transitions, 2015)
This paper examines the causal relationship between poverty reduction and economic growth in Swaziland during the period 1980-2011. Unlike some of the previous studies, the current study uses the newly developed ARDL-bounds testing approach to co-integration, and the ecmbased Granger causality method to examine this linkage. The study also incorporates financial development as a third variable affecting both poverty reduction and economic growth - thereby leading to a trivariate model. The results of this study show that economic growth does not Grangercause poverty reduction in Swaziland - either in the short run or in the long run. Instead, the study finds a causal flow from poverty reduction to economic growth in the short run. These findings, however, are not surprising, given the high level of income inequality in Swaziland. Studies have shown that when the level of income inequality is too high, economic growth alone may not necessarily lead to poverty reduction.
Keywords: poverty; Svazi; revščina; economic growth; gospodarska rast; Swaziland; ardl-bounds testing approach